ADDITION OF FRESHWATER MUSSEL FLOUR (Pilsbryoconcha exilis) ON MAKING OF COMPOSITE FLOUR COOKIES TOWARDS CONSUMER ACCEPTANCE - Fajar Theo; Dahlia Dahlia; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aims to determine consumer acceptance on making of composite flour cookies with adding different amounts of freshwater mussel (Pilsbryoconcha exilis) flour. The research methodology used was an experimental method with a non-factorial Completely Randomized Design. The treatment used in the study was the addition of freshwater mussel flour to composite flour cookies (0g, 20g, 30g, and 40g). The parameters were organoleptic value (appearance, aroma, texture, and taste) and proximate composition (water content, ash, fat, and protein content). The results showed the addition 20g of freshwater mussel flour (C2) treatment was most preferable by consumer acceptance, with the characteristics were brownish-yellow of appearance, good tasty, frangible, and typical aroma of freshwater mussel, with the content of water, ash, protein, and fat were 2.15%, 0.79%, 10.27%, and 31.27%, respectively. Keywords: Composites, Cookies, Freshwater Mussel, Organoleptic, Proximate